Assessment of traumas in children hospitalized in Department of Paediatric Surgery University Hospital no. 1 in Bydgoszcz in years 2005-2009 - Barczykowska, Ewa; Żurawska, Marika; Daniluk-Matraś, Irena; Grabinska, Marta; Kurylak, Andrzej (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2012)
Introduction: Traumas are the main cause of death and hospitalization in children and adolescents. The aim of this research was to assess the incidence of injuries in children treated at the Department of Paediatric Surgery University Hospital no. 1 in years 2005-2009. Material and methods : The analysis concerned 958 children hospitalized in the Department of Paediatric Surgery University Hospital no. 1 in years 2005-2009 because of trauma. The study had retrospective character. Data were obtained from medical history of children. Results : The study shows that boys are more likely to injuries than girls (61.17% vs. 38.83%). The largest group was children aged from 7-14. years of age (35.91%). Most children came from the city than from rural areas (72.13% vs. 27.87%). For most traumas took place at home (34.34%). The most common cause of injuries among newborns and infants and children aged 1 to 3. age was a fall from a height (respectively 65.42% and 45.63%), in the age group 4 to 6 age and 7-14 years of age the impact of the object (respectively 24.47%, 18.9%), and among adolescents aged 15-19 age beatings (20.55%) and road traffic accidents (18.97%). Children often got craniocerebral trauma (67.74%) and bone and joint injuries (18.67%). The vast majority of children (86.44%) needed conservative treatment and required to stay in hospital for 3 days (74.12%). Longer periods were associated with abdominal injuries. The majority of injuries in children (58.87%), were in the spring and summer months (April-September). Conclusions : Boys are more injuries than girls. Notwithstanding the age, children the most suffer from craniocerebral and bone and joint traumas. The causes of injuries in children are varied in different age groups. The vast majority of injuries that needed conservative treatment and required hospitalization lasted up to 3 days.